De novo neurogenesis by targeted expression of atoh7 to Müller glia cells - Lust, Katharina; Sinn, Rebecca; Pérez Saturnino, Alicia; Centanin, Lázaro; Wittbrodt, Joachim (Development, 2016)
Skip to Next Section - Regenerative responses in the vertebrate CNS depend on quiescent radial glia stem cells, which re-enter the cell cycle and eventually differentiate into neurons. The entry into the cell cycle and the differentiation into neurons are events of opposite nature, and therefore efforts to force quiescent radial glia into neurons require different factors. Here, we use fish to show that a single neurogenic factor, Atoh7, directs retinal radial glia (Müller glia, MG) into proliferation. The resulting neurogenic clusters differentiate in vivo into various retinal neurons. We use signaling reporters to demonstrate that the Atoh7-induced regeneration-like response of MG cells is mimicked by Notch, resembling the behavior of early progenitors during retinogenesis. Activation of Notch signaling in MG cells is sufficient to trigger proliferation and differentiation. Our results uncover a new role for Atoh7 as a universal neurogenic factor, and illustrate how signaling modules are re-employed in diverse contexts to trigger different biological responses.